A novel antimicrobial coating to prevent periprosthetic joint infection. Issue 12 (1st December 2020) - Ramalhete, Rita; Brown, Robyn; Blunn, Gordon; Skinner, John; Coathup, Melanie; Graney, Ian; Sanghani-Kerai, Anita
Abstract : Aims: Periprosthetic joint infection (PJI) is a debilitating condition with a substantial socioeconomic burden. A novel autologous blood glue (ABG) has been developed, which can be prepared during surgery and sprayed onto prostheses at the time of implantation. The ABG can potentially provide an antimicrobial coating which will be effective in preventing PJI, not only by providing a physical barrier but also by eluting a well-known antibiotic. Hence, this study aimed to assess the antimicrobial effectiveness of ABG when impregnated with gentamicin and stem cells. Methods: Gentamicin elution from the ABG matrix was analyzed and quantified in a time-dependent manner. The combined efficiency of gentamicin and ABG as an anti-biofilm coating was investigated on titanium disks. Results: ABG-gentamicin was bactericidal from 10 μg/ml and could release bactericidal concentrations over seven days, preventing biofilm formation. A concentration of 75 μg/ml of gentamicin in ABG showed the highest bactericidal effect up to day 7. On titanium disks, a significant bacterial reduction on ABG-gentamicin coated disks was observed when compared to both uncoated (mean 2-log reduction) and ABG-coated (mean 3-log reduction) disks, at days 3 and 7. ABG alone exhibited no antimicrobial or anti-biofilm properties. However, a concentration of 75 μg/ml gentamicin in ABG sustains release over seven days and significantly reduced biofilm formation. Its use as an implant coating in patients with a high risk of infection may prevent bacterial adhesion perioperatively and in the early postoperative period. Conclusion: ABG's use as a carrier for stem cells was effective, as it supported cell growth. It has the potential to co-deliver compatible cells, drugs, and growth factors. However, ABG-gentamicin's potential needs to be further justified using in vivo studies. Cite this article: Bone Joint Res 2020;9(12):848–856.